الذكاء الانفعالي والصّحة النفسية وعلاقتهما ببعض المتغيرات - إقروفة, صفية (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى معرفة العلاقة بين الذكاء الانفعالي والصّحة النفسية، وتأثيرهما على بعض المتغيرات(الجنس والتخصص الدراسي) لدى عينة من تلاميذ التعليم الثانوي، تكونت من(94) فردا، للعام الدراسي 2013/2014، تمّ اختيارها بالطريقة العشوائية البسيطة. استخدم فيها المنهج الوصفي الارتباطي طبق عليها مقياس الذكاء الانفعالي لإبراهيم الخولي(2010) ومقياس الصحة النفسية للباحث دياب عبد الله مروان(2005). توصلت إلى وجود علاقة ارتباطية بين الذكاء الانفعالي والصحة النفسية. وجود فروق ذات دلالة إحصائية في الدرجة الكلية للصحة النفسية حسب الجنس لصالح الإناث، وجود فروق ذات دلالة إحصائية في الدرجة الكلية للصّحة النفسية تعزى للتخصص الدراسي لصالح التخصص العلمي. وجود فروق ذات دلالة إحصائية في الدرجة الكلية للذكاء الانفعالي حسب الجنس لصالح الذكور، وجود فروق ذات دلالة إحصائية في الدرجة الكلية مقياس الذكاء الانفعالي تعزى للتخصص الدراسي لصالح التخصص الأدبي. The study aimed to identify the relationship between emotional intelligence and mental health, and their effect on some variables (gender and academic specialty) among a students of secondary school . the descriptive correlative approach method was used in this study. The sample consisted of (94)male and female students, for the academic year 2013-2014. it has been selected by the simple random way. the researcher used the emotional intelligence designed Kholi Scale(2010), and mental health scale adapted in the Palestinian environment by Marwan Abdullah (2005). The results includes the presence of statistically significant differences in the total score for Mental Health according to gender in favor of females, The presence of statistically significant differences in the total score of Mental Health attributed to allocate the school for the benefit of scientific specialty.The results includes The presence of statistically significant differences in the total score of emotional intelligence according to gender in favor of males, and the presence of statistically significant differences in the total score of emotional scale according to academic specialty in favor of literary specialty.
مقال
Keywords: الذكاء الانفعالي؛الصحة النفسي؛التعليم الثانوي; Emotional Intelligence; Mental Health; Secondary Education